Membranous Structure of Purified Escherichia coli Lipopolysaccharide - Katayama, Yutaka (1971)
The ultrastructure of the purified and lyophilized endotoxin from Escherichia coli O111 was observed by ultrathin sectioning. Onion-like globular membrane structures were observed in addition to rod-like and ribbon-like structures, indicating the existence of a globular membrane structure even in the dried state.